Aspects Influencing Personal Life and Health Insurance Purchase - Steve Matthew Sanjaya; Tuntun Salamatun Zen (PT. Publikasiku Academic Solution, 2023)
The study aims to identify the factors that influence the purchase decision of life & health insurance in Indonesia and determine how those factors influence. The method used in this study is qualitative method with semi-structured interviews. A total of 17 respondents were interviewed from insurance customers, non-insurance customers, and insurance agents in Bandung City. The result of this study indicates that demographic factors such as income level, assets, educational background, financial dependency, and health status directly influence life & health insurance purchase decisions. Insurance product benefits, price, trust in insurance companies, trust in insurance agents, and perceived value insurance were found to influence life & health purchase decisions too directly. Additionally, multiple factors were found to influence insurance trust. These factors include the insurance company brand, selling practices used by insurance agents, perceived service quality of insurance, and insurance literacy. Furthermore, insurance perceived value was also influenced by other factors such as insurance literacy, culture, and environment. Above all aspects, the insurance agents have direct control over the selling practices, service quality, and insurance literacy that someone experience. This study also proved that insurance agents were responsible for the insurance industry’s bad reputation in Indonesia. This result will equip insurance agents to know their customers better and adjust their selling practices to suit potential customers. Insurance agents are also strictly prohibited from mis-selling insurance products.